SOD1 gene screening in ALS: frequency of mutations, patients’ attitudes to genetic information and transition to tofersen treatment in a multi-center program - Meyer, Thomas; Schumann, Peggy; Grehl, Torsten; Weyen, Ute; Petri, Susanne; Rödiger, Annekathrin; Steinbach, Robert; Großkreutz, Julian; Bernsen, Sarah; Weydt, Patrick; Wolf, Joachim; Günther, René; et al. (Amyotrophic lateral sclerosis & frontotemporal degeneration, 2025)
To report the frequency of pathogenic SOD1 gene variants in a screening program in amyotrophic lateral sclerosis (ALS), and the clinical practice of transition to an expanded access program (EAP) of tofersen treatment. From October 2021 to February 2024, at 11 ALS centers in Germany genetic testing for SOD1, FUS, TARDBP, and C9orf72 was performed. Patients were offered to opt for notification either about all genetic variants or SOD1 variants relevant for tofersen therapy. The transition to the EAP with tofersen was assessed. 1935 patients were screened (94.7% sporadic ALS). 48.8% (n = 928) opted for notification of treatment-relevant information. Genetic variants were found as follows: SOD1 (likely) pathogenic variants (class 4/5) 1.8% (n = 34), variants of unknown significance (class 3) 0.8% (n = 16), FUS (class 4/5) 0.9% (n = 17), TARDBP (class 4/5) 1.3% (n = 25), C9orf72 hexanucleotide repeat expansion 7.0% (n = 135). In SOD1-ALS (encompassing class 3-5 variants, n = 50), 68.0% (n = 34) reported a negative family history. 74.0% (n = 37) of SOD1-ALS patients - which represent 1.9% of all participants of the screening program - were transitioned to tofersen. Median duration from start of genetic testing to treatment was 94 days (57 to 295 days). Eight patients declined treatment whereas five individuals died before initiation of therapy. The finding of SOD1 variants in patients with a negative family history underscores the need for a broad genetic screening in ALS. In SOD1-ALS, the treatment option with tofersen was mostly utilized. The wide range in the transition time to tofersen calls for a SOD1-ALS management program.
Online veröffentlicht: 13. September 2024
Gesehen am 21.01.2025